ELECTRICAL METHOD OF DELIVERING HYALURONIC ACID THROUGH THE SKIN (2018)
An electrical method of delivering hyaluronic acid through the skin that includes applying a selected electroporation pulsatile current stimulus, from any device and/or support comprising at least one electrode, the electroporation pulsatile current stimulus being of a character and for a duration sufficient to transdermally deliver hyaluronic acid, for example an aqueous composition, to a biological subject, and transporting different rates of hyaluronic acid across the skin in accordance to the selected current mode.